NEW APPROACHES TO SOCIAL POLICY IN GEORGIA - Gerzmava, Otar; Gorgiladze, Levan (European Scientific Journal, ESJ, 2014)
The majority of developed countries and several developing countries have created, and are regularly updating, their national health policies. This is especially important for social and economic development. In Georgia, as in other developing countries, the main objective of the health reform process is a comprehensive policy. It is based on the main priorities of the nation’s health problems, and targets specific areas to be addressed and corrected over several years.